การกำจัดสังกะสีจากดินปนเปื้อนน้ำมันเครื่องใช้แล้วโดยสารลดแรงตึงผิว - รุจิเรข จันทร์อำไพ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
This experiment was done to determine the efficiency of two types of surfactant, which were anionic (Dowfax 8390) and non-ionic (Triton X-100) in order to remove zinc from soil contaminated with used lubricant oil. The concentration of surfactant was varied from 1, 2, 5 and 10 times of critical micelle concentration (CMC). Each concentration was done under different pH of 5 and 10 to compare with natural condition without pH adjustment. Studied soil was loamy-sand. This soil is practical for soil washing to remediate. Used lubricant oil was taken from gas station containing 1,390 ppm of zinc. The experiment was done in batch test. Result from the experiment showed good efficiency fo dissolving hydrocarbon into water so that zinc was able to remove. The amount of zinc that was dissolved in oil and adsorbed into soil was the same, therefore using surfactant with micelle properties promote the solubility of non-polar substance. The removal efficiency of zinc was increased when using higher surfactant concentration. Anionic surfactant gave more capability of removing zinc than non-ionic surfactant. Zinc removal efficiency was higher in natural condition followed by at pH 10 and 5, respectively. After washing soil for three times by anionic surfactant at 10 times of CMC, zinc removal efficiency reached to 87%.